Lymph node metastasis from atypical meningioma: case report (Research, Society and Development, 2023)
The meninges are connective tissue structures that surround the central nervous system (CNS) and their functions include mechanical protection and formation of the blood-brain barrier. In turn, meningiomas are CNS tumors, mostly benign, which originate from non-epithelial precursor cells of the meninges. The aim of this paper is to describe an uncommon case in the medical literature: the incidence of metastasis from a grade II cranial meningioma to a lymph node in the cervical chain. Thus, we report the case of an elderly man who underwent a computed tomography of the skull after a mild domestic incident, which showed the existence of an intracranial tumor, the patient being asymptomatic. From then on, the investigation began, leading to the diagnosis of post-biopsy meningioma. Months later, an abnormal bulge in the cervical region was observed, leading to a new investigation and a new diagnosis: grade II meningioma associated with lymph node metastasis. The surgical approach seems to be preferred in progressively growing, recurrent and symptomatic meningiomas; the association with biological therapies, such as somatostatin analogues, can delay its growth.